A Slap at the Charleys or a Tom & Jerry lark -vide New Poliece Bill. - Heath, William, 1795-1840 - also known as Paul Pry (McLean, Thomas, 1829)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Nightwatchmen; Brawl; Peel, Robert, 1788-1850; Wellington, Arthur Wellesley, Duke of, 1769-1852; Lyndhurst, John Singleton Copley, Baron, 1772-1863; Great Britain. Metropolitan Police Office -- History